Prevalence and Associated Factors of Intestinal Parasitic Infections in Selected Areas of Mugum Karmarong Rural Municipality - Kamal Singh Kathayat; Ravin Bhandari; Maya Rai; Shandiya Chaulagai; Pema Gyamjo Lama (Nepal Journal of Public Health, 2026)
Background: Parasitic infection is still a serious public health problem in the world. Intestinal parasites infect about 3.5 billion people, and these infections cause illness in 450 million children. In Nepal, intestinal parasitic infections which are most prevalent in children and are the major public health problem. The objective was to study the prevalence and associated factors of intestinal parasitic infection among the people living in the selected area of Mugum Karmarong Rural Municipality. Methodology: Community based Quantitative cross-sectional studywas carried out in selected area of Mugum Karmarong Rural municipality, Mugu district. Total 250 stool sampleswere collected randomly and the stool samples wereexamined by direct smear method. Systematic Random Sampling was used and sampling unit was the individual who provided the stool sample. Results: Among 250 adult people 21 were found to be positive.The prevalence rate of intestinal parasitic infection among the people living in selected area of Mugum Karmarong Rural Municipality was 8.4%. Parasites detected were Tania Saginat, Ascaris lumbricoides ,Trichuris trichuira, Anchylostoma duodenale, E. Histolyticaand H. nana. Conclusions: Proper distribution of anti-helminths drugs, good personal hygiene, good sanitation and basic knowledge regarding intestinal parasitic infection showed protective effect whereas, consumption of rawmeat causes parasitic infection. Awareness programabout the parasitic infections or mode of transmissionsshould be run. Consumption of raw meat should be strictly discouraged and properly cooked meat should be consumed.